1984
DOI: 10.1111/j.1469-7610.1984.tb01721.x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Maternal Depression and Child Behaviour Problems

Abstract: Using a random sample of first-time mothers from an inner London borough, the relationship was examined between maternal depression and child behaviour problems at various stages after the birth of the child. Child problems at 14 months were unrelated to present or past maternal depression. Child problems at 27 and 42 months were related in an interactive way with present and past depression. There was little indication of behaviour problems preceding maternal depression. An examination of possible confounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
87
1
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(100 citation statements)
references
References 8 publications
(7 reference statements)
9
87
1
3
Order By: Relevance
“…We analyzed scores for items specifically addressing externalizing-type difficulties (temper tantrums and hard-to-manage behaviors). The scale has previously been shown to have external validity (as evidenced by associations with other indices of child behavior problems and discrimination of high versus low risk groups) (Ghodsian, Zajicek, & Wolkind, 1985;Murray, 1992;Halligan et al, 2013) and acceptable reliability (Ghodsian et al, 1984;Richman & Graham, 1971). Internal consistency for the externalizing scale used in the current study was acceptable (α = .78).…”
Section: Child Measuresmentioning
confidence: 82%
See 1 more Smart Citation
“…We analyzed scores for items specifically addressing externalizing-type difficulties (temper tantrums and hard-to-manage behaviors). The scale has previously been shown to have external validity (as evidenced by associations with other indices of child behavior problems and discrimination of high versus low risk groups) (Ghodsian, Zajicek, & Wolkind, 1985;Murray, 1992;Halligan et al, 2013) and acceptable reliability (Ghodsian et al, 1984;Richman & Graham, 1971). Internal consistency for the externalizing scale used in the current study was acceptable (α = .78).…”
Section: Child Measuresmentioning
confidence: 82%
“…The version used in the current study comprised a reduced set of 8-items which has previously been found to be appropriate for children in the current study age range (Murray, 1992;Ghodsian, Zajicek, & Wolkind, 1984). We analyzed scores for items specifically addressing externalizing-type difficulties (temper tantrums and hard-to-manage behaviors).…”
Section: Child Measuresmentioning
confidence: 99%
“…The first of these was conducted by Ghodsian et al (1984). The mental state of a community sample of women recruited antenatally had been systematically assessed on a number of occasions up to 42 months postpartum.…”
Section: Emotional/social Functioningmentioning
confidence: 99%
“…However, only two studies of which we are aware have examined the timing of exposure to maternal depression over a longer period. One prospective study of 131 mothers found that maternal depression reported at 14 months postpartum was more predictive of child behavior disturbance than was maternal depression reported at either 27 or 42 months postpartum (Ghodsian, Zajicek, & Wolkind, 1984). In a retrospective study, Alpern and Lyons-Ruth (1993) found that type of child maladjustment was differentially associated with timing of maternal symptoms, such that postpartum-only depression was more associated with anxiety symptoms and recent depression-only predicted hyperactivity symptoms.…”
mentioning
confidence: 99%